Áp dụng phương pháp kế toán chi phí dựa trên hoạt động cho các công ty niêm yết tại thị trường chứng khoán Việt Nam - Đào Thị Thu, Giang; Trần Tú, Uyên (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2016)
Activity-based costing (ABC) was initiated by Johnson and Kaplan (1987) as an advanced technique in cost estimating processes. The method, since its introduction, has been widely applied and perceived as an effective tool to manange and estimate firm costs, but it is not commonly adopted in Vietnam. This paper, aiming to analyze the factors influencing the ABC practices among listed enterprises in Vietnam’s stock market, draws a few suggestions for motivating Vietnamese firms to further employ the approach.
Keywords: management accounting; ABC; cost center; traditional standard costing (TSC)